Oriented Functionalization of Natural Hollow Kapok Fiber for Highly Efficient Removal of Toxic Hg(II) from Aqueous Solution - Wang, Feng; Zheng, Yian; Zhu, Yongfeng; Wang, Aiqin (Frontiers in Environmental Science, 2016)
Due to hollow and tubular structure, a natural kapok fiber (KF) was used as the support and orientation matrix to control the polymerization of ethyleneglycol dimethacrylate (EGDMA) and N-vinylimidazole (VIM) along its inherent axial surface via a facile in situ rapid polymerization reaction in air atmosphere. The as-formed KF@VIM/EGDMA composite is featured with porous surface and rich N-containing functional groups for potential application as a highly efficient adsorbent for removal of toxic Hg(II) from aqueous solution. The variables affecting the adsorption capacity were studied, including monomer ratio, external pH values, contact time, and initial Hg(II) concentration. The pseudo-second-order equation and two adsorption isotherms including Langmuir and Freundlich equations were applied to determine the adsorption kinetics and adsorption capacity. The results show that the as-prepared KF@VIM/EGDMA composite has a maximum adsorption capacity of 697 mg/g to Hg(II), while no appreciable adsorption capacity can be found for KF itself. Given its intrinsic large lumen, faster adsorption kinetics (45 min) are also expected and observed for KF@VIM/EGDMA. After a simple filtration, this adsorbent can be directly separated from the aqueous solution and then be regenerated for multi-cyclable utilization. During the adsorption process, the chemical complexing represents the main adsorption mechanism. As a naturally renewable KF, such a simple preparation method opens a new avenue to develop highly efficient and economically viable adsorbent for removal of toxic heavy metal from aqueous solution.